Effect of off-road vehicle activity on vegetation community and soil properties in the Otindag Sandy Land, China - Wang, Xuanxuan; Long, Jinghua; Zhang, Wei; Cao, Xinrui; Liang, Shuang; Gao, Hui; Yang, Jintian (Frontiers in Environmental Science, 2025)
Off-road vehicle (ORV) activity has emerged as a growing ecological disturbance in arid and semi-arid grasslands, yet its combined impact with topographic factors such as slope remains poorly understood. A 4-year field compaction test was conducted in Otindag Sandy Land to explore changes in the vegetation community and soil properties under different degrees of off-road vehicle compaction and different slope conditions and investigate the effect of ORV activity on grassland vegetation and soil. The results showed that ORV activity caused a marked reduction (P < 0.05) in plant community species diversity, and the Shannon–Wiener (SWI), Margalef’s (MI), Simpson dominance (SDI), and Pielou evenness (PEI) indices decreased by 58.62%–81.31%, 24.44%–48.78%, 52.22%–77.78% and 50.00%–75.68%, respectively, in ORV treatments compared to that in the control treatments. Additionally, ORV activity caused a significant increase in soil bulk density and a notable decrease in soil organic matter, water and clay contents, available phosphorus and potassium, and soil enzyme activity. Redundancy analysis showed that the species diversity of the plant community was closely related to soil factors. MI, SWI, SDI, and PEI were positively correlated with pH, available phosphorus and potassium, alkali-hydrolyzable nitrogen, soil organic matter, and soil water, silt, and clay contents and negatively correlated with bulk density and sand content. The slope and ORV activity interacted significantly with the Simpson dominance index, soil particle composition, pH, total nitrogen, alkali-hydrolyzable nitrogen, soil sucrase activity, and solid-urease activity. The impact of ORV activity on the vegetation community and soil properties became more severe with an increase in the slope. Assessing the impact of ORV activity on soil and vegetation can provide a scientific basis for the sustainable development and management of outdoor cross-country activities.